Salt extraction from lime-based mortars: An experimental study using different poultice formulations. (20th September 2020) - Randazzo, L.; Montana, G.; Castiglia, A.; La Russa, M.F.
Highlights: Soluble salts extractive capability of commercial poulticing materials. Pore-size distributions influence the efficiency of soluble salts removal. The obtained data provide an operating protocol for the restoration sector. Abstract: The extractive capability of soluble salts in poultices treatments currently used in mortar conservation (Arbocel TM plus sepiolite; Arbocel TM, sepiolite and sand; Westox-Cocoon®) were tested to evaluate their efficiency and compatibility with specific mortar substrate. The pore size distribution of the experimental mortar substrate and of the blank dried poultices were preliminarily accomplished by mercury intrusion porosimetry (MIP). Desalination tests were carried out on specifically-formulated mortars after capillary absorption of Na2 SO4 0.3 M solution. The efficiency of salt extraction was measured by means of electrical conductivity meter and ion chromatography. Among the tested products, Westox-Cocoon® showed the best performance in terms of the ability to extract soluble salts. It is the only poultice with a porosity distribution characterised by predominantly large macropores (20–30 µm), which guarantees it an extraordinary efficiency in the first phase of the extraction process (wetting/dissolving). This last aspect provides a useful term of comparison for conservators who actually use these products and a base of operational protocol more suitable to the needs of the restoration site.